Goiter and Its Associated Factors among Adolescent High School Girls at Tach Armachiho District, Northwest Ethiopia: An Institution-Based Cross-Sectional Study - Belaynew Mesfin; Bisrat Misganaw; Melkamu Tamir Hunegnaw; Esmael Ali Muhammad (Journal of Nutrition and Metabolism)
Introduction. In Ethiopia, iodine deficiency disorder (IDD) is a major public health problem. The most visible effect of IDD is the appearance of goiters, and 28 million people are affected by goiter. Therefore, this study aimed to assess the prevalence and associated factors of goiter among high school adolescent girls at Tach Armachiho district, Northwest Ethiopia. Methods. An institution-based cross-sectional study was conducted from October to November 2018. A total of 620 high school adolescent girls were selected using the simple random sampling technique, and structured questionnaires having observational check-list were used for data collection. The presence of goiter was estimated using criteria set by World Health Organization. Iodine content of the salt was estimated by using spot testing kits. Both bivariable and multivariable logistic regressions were used to identify associated factors. The degree of association between independent and dependent variables was assessed by using odds ratio with 95% confidence interval. Those variables having p value of less than 0.05 in the multivariable analysis were considered as significant factors for goiter. Results. A total of 614 adolescent girls gave a complete response. The prevalence of goiter among adolescent girls was 24.1%. In the multivariable logistic regression analysis, age of adolescent girls (adjusted odds ratio (AOR) = 1.57, 95% CI: 1.01–2.46), residence (AOR = 1.91, 95% CI: 1.04–3.51), family history (AOR = 4.96, 95% CI: 3.19, 7.72), low dietary diversity (AOR = 8.39, 95% CI: 4.36–16.14), and medium dietary diversity (AOR = 2.26, 95% CI: 1.36–3.77) were significantly associated with adolescent girls goiter. Conclusions. Goiter among high school adolescent girls in this study was high. Age of adolescent, residence, family history of goiter, and dietary diversity were statistically significant factors for goiter. Therefore, more emphasis will be given for late adolescent age, having family history of goiter, low dietary diversity, and rural residence to improve the burden of adolescent goiter.